The Influence of Comic Media on Social Studies Learning Outcomes Theme Caring for Living Creatures Environmental Materials as Resources Class IV SD N 94 Singkawang - Chindy Natalistha; Fajar Wulandari; Dina Anika Marhayani (CV. Rayyan Dwi Bharata, 2024)
This research aims to: 1) Find out whether there is an increase in social studies learning outcomes with the theme of caring for living things, environmental material as a resource between classes that use comic media and classes that use conventional media, 2) How big is the difference in social studies learning outcomes with environmental material as a resource? class students who use comic media and classes who use conventional media. The type of research used is quantitative research with experimental research methods. The research design used was a quasi experimental design with a pretest-posttest form. The data analysis technique used in this research is the two-sample t test to improve social studies learning outcomes between classes that use comic media and classes that use conventional media, seen from the results of calculating post-test and pre-test class learning outcomes using the N test. -Gain shows that there is an increase of 0.68 in the medium category (2) there is a difference of 0.68 in social studies learning outcomes on the theme of caring for living things, environmental materials as a resource between classes that use comic media and classes that use conventional media, if you look at it from the results of calculations on the learning outcomes of the experimental class using the two-sample T test, it shows that tcount = 7.05890 ttable = 2.01290 with a significance level of 5%, meaning that Ha is accepted and Ho is rejected;